2015
DOI: 10.1371/journal.pone.0130588
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of the Large-Conductance, Ca2+-Activated K+ (BK) Channel Shortens Action Potential Duration in HL-1 Cardiomyocytes

Abstract: Long QT syndrome is characterized by a prolongation of the interval between the Q wave and the T wave on the electrocardiogram. This abnormality reflects a prolongation of the ventricular action potential caused by a number of genetic mutations or a variety of drugs. Since effective treatments are unavailable, we explored the possibility of using cardiac expression of the large-conductance, Ca2+-activated K+ (BK) channel to shorten action potential duration (APD). We hypothesized that expression of the pore-fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
8
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 36 publications
4
8
1
Order By: Relevance
“…Support for this idea came from a study describing the electrophysiological function of BK Ca in HL-1 cells by viral overexpression, a cell line derived from a murine atrial tumor. BK Ca overexpression reduced the very short AP of this murine model by 50% (APD 90 from 30 to 14 ms) and was proposed as a potential genetic therapy to reduce AP duration (APD) of the LQT syndrome [13]. In contrast to the experiments in HL-1 cells, we observed that in hiPSC-CMs, the presence of BK Ca induces oscillations in the early plateau phase and no speed-up in the final repolarization [13].…”
Section: Discussioncontrasting
confidence: 67%
See 2 more Smart Citations
“…Support for this idea came from a study describing the electrophysiological function of BK Ca in HL-1 cells by viral overexpression, a cell line derived from a murine atrial tumor. BK Ca overexpression reduced the very short AP of this murine model by 50% (APD 90 from 30 to 14 ms) and was proposed as a potential genetic therapy to reduce AP duration (APD) of the LQT syndrome [13]. In contrast to the experiments in HL-1 cells, we observed that in hiPSC-CMs, the presence of BK Ca induces oscillations in the early plateau phase and no speed-up in the final repolarization [13].…”
Section: Discussioncontrasting
confidence: 67%
“…Recently, overexpression of non-cardiac BK Ca in CMs was proposed as a treatment for LQTS [13], since BK Ca is a hyperpolarizing channel, which might shorten human AP. Support for this idea came from a study describing the electrophysiological function of BK Ca in HL-1 cells by viral overexpression, a cell line derived from a murine atrial tumor.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This may be a contributing factor to the substantial reductions (∼70%) in atrial I CaL that are typically seen in patients with persistent AF. 42 While initially adaptive, increased expression of human K Ca 1.1 has been shown to shorten the action potential duration in HL-1 atrial cardiomyocytes, 43 and this could increase the propensity for initiation and maintenance of AF via re-entry mechanisms. The phosphodiesterase-III inhibitor, milrinone, is a heart failure therapy that has recently been shown to cause K Ca 1.1dependent dilatation of the pulmonary veins.…”
Section: Discussionmentioning
confidence: 99%
“…Taken together, these findings indicate that K Ca 1.1 excess, as well as K Ca 1.1 deficiency can have deleterious effects on cardiac function and have implications for administration of K Ca 1.1 activating drugs, which have been proposed as potential therapies for long QT syndrome and ischemiareperfusion injury. 43,46 Pharmacological manipulation of K Ca 1.1 activity warrants investigation as a new treatment option for cardiac arrhythmias and myopathies, but as for many other cardiac ion channels, there may be a narrow beneficial therapeutic range. lines showed increased peaks per event and higher event duration compared to controls (see Table VIII in the Data Supplement); Y axis: voltage (mV), X axis: time (ms).…”
Section: Discussionmentioning
confidence: 99%